The effect of radiation on the chronology of extraction wound healing. Histomorphologic study in rats - Raveli, D. B.; Ferreira, B. A.; Cordeiro, R. C.; Okamoto, T.; Gabrielli, M. F. (My University, 1990)
The purpose of this study was to analyse histomorfologically the X-radiation influence on the chronology of wound healing of tooth extraction. Sixth young albino rats were used. After extracting the maxillary right incisors all the rats, three experimental groups were formed: the control (I) and the groups that received 1.25 Sv (II) and 1.75 Sv (III). The rats were killer at 3, 7, 14 and 28 post-operative days following the teeth extraction. The pieces obtained were submitted to routine laboratorial procedures until getting pieces stained with hematoxylin and eosin. It was concluted that: 1) there was a delay in the epithelial proliferation of the gengival mucosa o the animals submitted to X-rays, in a similar way in the two irradiated groups: 2) there was a considerable delay in the alveolar repair process in dental extraction wound; 3) this delay was more proeminent when the X-ray action was more intense.
Influência da radiação X na cronologia do processo de reparo em feridas de extração dental. Estudo histomorfologico em ratos.